Manajemen Risiko Operasional Dalam Industri Perbankan Syariah: Studi Literatur - Putri Wulandari Nasution; Tria wulandari; Muhammad Rizal (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
This study aims to examine the concept, causal factors, application, and mitigation strategies of operational risk in the Islamic banking industry through a literature study approach. The method used is a literature review with secondary data sources including scientific journals, textbooks, OJK/Bank Indonesia regulations, and previous research published between 2017–2024. The results show that operational risk in Islamic banks originates from four main factors: internal process failure, human error, information technology system failure, and external factors. The implementation of operational risk management in Islamic banking is mandated through POJK Number 65/POJK.03/2016, covering risk identification, measurement, monitoring, and control. Effective mitigation strategies include strengthening internal control systems, improving human resource quality, managed digital transformation, and active supervision by the Sharia Supervisory Board (DPS). This research is expected to serve as a theoretical and practical reference for the Islamic banking industry in addressing increasingly complex operational risk challenges.